2008
DOI: 10.1007/s10877-008-9119-y
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive Cardiac Output by Transthoracic Electrical Bioimpedence in Post-cardiac Surgery Patients: Comparison with Thermodilution Method

Abstract: Thoracic electrical bioimpedance cardiac output compares favorably with thermodilution method among post-cardiac surgery patients. Further studies are indi- cated with this instrument to validate its efficacy in various clinical situations and utility in monitoring hemodynamic interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 13 publications
2
25
1
Order By: Relevance
“…The percentage error of TEB (T-1) when the chest was closed is 30% and at T-2 when chest was open is 32% which demonstrate that sternotomy had little or no effect on the cardiac output reading which remain consistently same and comparable with that of TDCO [16]. Our results are similar from those reported by Sageman et al [17], Gujjar et al [18], Suttner et al [19], and Chakravarthy et al [20], who found TEB technology accurate and interchangeable with TD in post cardiac surgical patients.…”
Section: Discussionsupporting
confidence: 89%
“…The percentage error of TEB (T-1) when the chest was closed is 30% and at T-2 when chest was open is 32% which demonstrate that sternotomy had little or no effect on the cardiac output reading which remain consistently same and comparable with that of TDCO [16]. Our results are similar from those reported by Sageman et al [17], Gujjar et al [18], Suttner et al [19], and Chakravarthy et al [20], who found TEB technology accurate and interchangeable with TD in post cardiac surgical patients.…”
Section: Discussionsupporting
confidence: 89%
“…[21,22] TEB monitoring has shown inaccurate results in COPD patients, as changes in pulmonary vascular flow and intrathoracic pressure along with hyperinflation, may change the passage of current emitted by TEB device through chest and thus modify the aortic component of dZ/dt. [23] Our results are somewhat different from those reported by Sageman et al, [9] Gujjar et al, [24] Suttner et al, [25] and Chakravarthy et al, [26] who found TEB technology to be accurate and interchangeable with TD in post-cardiac surgical patients. However, assessment of CO during spontaneous breathing was not done in their studies.…”
Section: Discussioncontrasting
confidence: 89%
“…The accuracy and reproducibility of the results have repeatedly been confirmed in studies demonstrating that CO measured by TEB correlate closely, and with clinically acceptable agreement and precision, compared with CO measurements obtained by pulmonary artery thermodilution among both stable and unstable post-cardiac surgery patients [12, 13]. Advantages of TEB are that it is non-invasive in nature, it is not as time consuming as echocardiography, and does not require the training or skill required for either PAC or echocardiography [14].…”
Section: Introductionmentioning
confidence: 82%